Brazilian Ex-Slaves' Return to Africa: Xvii-Xix Historiography - Ilana Peliciari Rocha (Revista Brasileira Multidisciplinar - ReBraM /Brazilian Multidisciplinay Journal, 2013)
The article is about Brazilian communities of ex-slaves who returned to Africa and proposes a change of the historiographic perspective, which considers the interrelationship between the history of both continents. The Africans who returned from Brazil, in the 17th and 19th centuries, took with them the experience in Brazil and influenced their new African communities. Based on this theme, this paper presents the main discussions of historiography, pointing out aspects such as: culture, religion, family, the political and economic integration, the issue of ethnicity and identity. It presents a review of classic and current studies on the theme and its reflections and demonstrates the contribution of historiography to the advancement of the knowledge of the African diaspora. The analysis is bibliographical and considers the period of African slavery in Brazil.